ANALISIS LAPORAN ARUS KAS DI KOPERASI SIMPAN PINJAM LESTARI KOTA LUBUKLINGGAU - Herman Paleni; Metti Triana (LPPM UNIVERSITAS BINA INSAN, 2019)
Research aims to understand cash flow report in the cooperative Lestari Lubuklinggau savings and loans. Methods used in this study descriptive use of quantitative data analysis technique used cash flow, the calculation of data the ratio of cash flow and the ratio of investment and funding. Data collection technique using a technique observation and documentation. In obtained data use secondary data with the object research financial report loan and save cooperative lestari lubuklinggau during the past 5 year from 2014 until 2018. The results of this study are based on the calculation of cash flow data showing the cash flow of operating, investing and financing activities has increased / decreased every year. Based on the cash flow ratio shows the ratio of operating cash flow to interest and to net income in good condition because it has a large ratio of more than one. The ratio of operating cash flows to capital expenditures, to current debt and to total debt must be paid more attention because it has a ratio of less than one.